A review on endocrine disruptors and their possible impacts on human health - Kabir, Eva Rahman; Rahman, Monica Sharfin; Rahman, Imon (© 2015 Elsevier, 2016)
This article was published in Environmental Toxicology and Pharmacology [© 2015 Elsevier] and the definite version is available at: http://ac.els-cdn.com/S1382668915300120/1-s2.0-S1382668915300120-main.pdf?_tid=d5159a04-b538-11e6-896c-00000aacb362&acdnat=1480316818_f9b89a84cd4da21a57f6ff9c6a98c96a The article website is at: http://www.sciencedirect.com/science/article/pii/S1382668915300120